Le contrôle judiciaire de la procédure administrative : éléments de droit comparé, fédéral, ontarien et québécois - Robardet, Patrick (Les Cahiers de droit, 1982)
The exercise of diverse powers whether « administrative » or judicial or quasi-judicial by administrative bodies, raises many procedural issues. This article approaches them from a comparative point of view, hocking at selected cases from of Ontario and Quebec courts and the Federal Court of Canada. The cases studied concern the judicial control of administrative procedure followed by central institutions (that is, the Crown, governmental departments and administrative agencies, commissions or boards) in the three systems of law mentioned. A comparative approach permits us to identify existing trends in the immense body of day-to-day decisions made by the courts. Thus, with respect to the many procedural questions raised by administrative and governmental decision-making, elements of convergence or divergence can be identified in the judicial answers given to practical issues.